1988
DOI: 10.1007/bf00004862
|View full text |Cite
|
Sign up to set email alerts
|

Fishes of a subtropical Australian saltmarsh and their predation upon mosquitoes

Abstract: SynopsisThe fishes occurring in a subtropical Australian saltmarsh were studied from January to December 1984 to determine the seasonal abundance and feeding of the most common species. Wide variations in pool water levels and salinity were recorded. Eight species of fish were collected, four of which are of economic importance to fisheries. Three taxa, Gambusia affinis, Pseudomugil signifer, and gobiids predominated in terms of abundance and occurrence. The abundance of fishes fluctuated markedly on a seasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 15 publications
0
32
0
1
Order By: Relevance
“…Average food consumption and presumably time spent foraging by individual Gambusia also varies seasonally, with a peak in summer and a trough in winter (Morton et al, 1988). Morton et al (1988) found that in winter most Gambusia stomachs were empty, suggesting that most individuals were not feeding at all at the time, while a few stomachs were full, suggesting that these few individuals were feeding extensively.…”
Section: Foraging Diet Food Consumption Digestion and Food Conversionmentioning
confidence: 97%
See 1 more Smart Citation
“…Average food consumption and presumably time spent foraging by individual Gambusia also varies seasonally, with a peak in summer and a trough in winter (Morton et al, 1988). Morton et al (1988) found that in winter most Gambusia stomachs were empty, suggesting that most individuals were not feeding at all at the time, while a few stomachs were full, suggesting that these few individuals were feeding extensively.…”
Section: Foraging Diet Food Consumption Digestion and Food Conversionmentioning
confidence: 97%
“…They forage throughout the day (Belk and Lydeard, 1994), with analysis of stomach contents suggesting two diurnal peaks in feeding activity, one in the morning and another around dusk (Hess and Tarzwell, 1942;Walters and Legner, 1980). Average food consumption and presumably time spent foraging by individual Gambusia also varies seasonally, with a peak in summer and a trough in winter (Morton et al, 1988). Morton et al (1988) found that in winter most Gambusia stomachs were empty, suggesting that most individuals were not feeding at all at the time, while a few stomachs were full, suggesting that these few individuals were feeding extensively.…”
Section: Foraging Diet Food Consumption Digestion and Food Conversionmentioning
confidence: 99%
“…Initial work in Australia was done in single tidal creeks that drained the saltmarsh flats (Gibbs 1986, Morton et al 1987, Davis 1988, and in semi-permanent pools that remain on the flats after the tide has receded (Gibbs 1986, Davis 1988, Morton et al 1988. None of these studies, however, investigated whether fish actually occurred on the intertidal saltmarsh flats.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to control mosquito populations include habitat modification to maintain or restore tidal flooding, chemical control using non-specific chemicals to limit the abundance of adult mosquitoes, and biological control facilitated by the consumption of larvae by fish and shrimp (Morris et al 2002;Morton et al 1988;Morton et al 1987). Pseudomugil signifer, a small fish commonly found in saltmarsh, was found in laboratory studies to prey on mosquito larvae but was satiated at moderate densities (Willems et al 2005).…”
Section: Carbon and Aquatic Foodwebsmentioning
confidence: 99%